The impact of obesity on left ventricular mass and left ventricular systolic function in children - Ria Nova; Bambang Madiyono; Sudigdo Sastroasmoro; Damayanti R Sjarif (Indonesian Pediatric Society, 2005)
Background Obesity causes cardiovascular disturbances. Theincidence of cardiovascular disease is higher even in mildly obesepatients than in lean subjects.Objectives The purpose of this study was to compare left ven-tricular (LV) mass, LV internal dimensions, and LV systolic func-tion between obese and normal children; and to determine the as-sociation of the degree of obesity with LV mass and LV systolicfunction.Methods This cross-sectional study was conducted on elemen-tary school students in Jakarta from February to April 2003. Wemeasured the subjects’ body weight and height, and performedlipid profile and echocardiography examinations. Measurementsof LV mass, LV internal dimensions with regard to septum thick-ness, LV internal diameter, and LV posterior wall thickness; andLV systolic function as indicated by shortening fraction and ejec-tion fraction, were performed echocardiographically. The differ-ences in measurements between obese and normal children aswell as between obese children with and without lipid abnormalitywere analyzed. The correlation between the degree of obesity withLV size and systolic function was determined.Results Twenty-eight normal children and 62 obese children wereenrolled in the study. Mean LV mass was 35.7 (SD 5.16) g/cm 3 inobese children versus 24.0 (SD 3.80) g/cm 3 in normal children(P<0.0001). Mean septum thickness was 0.8 (SD 0.14) mm inobese children versus 0.6 (SD 7.90) mm in normal children (P<0.0001). Mean posterior wall thickness was 0.9 (SD 0.14) mm inobese children versus 0.6 (SD 9.97) mm in normal children(P<0.0001). Mean LV internal diameter was 4.0 (SD 0.34) mm inobese children versus 3.9 (SD 0.29) mm in normal children(P=0.300). There was strong correlation between the degree ofobesity and LV mass (r=0.838, P<0.0001). LV systolic function(shortening fraction) was 37.1 (SD 4.20) percent in obese childrenversus 35.8 (SD 4.99) percent in normal children (P=0.19). Ejec-tion fraction was 67.4 (SD 5.32) percent in obese children versus65.5 (SD 6.29) percent in normal children (P=0.13). There wasweak correlation between LV systolic function and the degree ofobesity (shortening fraction r=0.219, P=0.038; ejection fractionr=0.239, P=0.023).Conclusions Obese children had significantly greater LV mass,septum thickness, and posterior wall thickness than normal chil-Backgrounddren. Such significant difference was absent for LV internal diam-eter and measures of LV systolic function. There was no signifi-cant difference in LV mass and LV systolic function between obesechildren with or without abnormality of lipid profile. A strong corre-lation exists between the degree of obesity and LV mass, but thecorrelation between degree of obesity and LV systolic function wasweak